Validação de tecnologia para avaliação do teste do reflexo vermelho - Aguiar, Adriana Sousa Carvalho de (2010)
Due to its relevance for public health, the red reflex test, also known as little eye test, has become an established strategy to prevent infant blindness within a multi professional team work, involving the nurse in particular. Applied technologies in this context constitute a useful tool for the professional and their use has to be stimulated aiming the assistance improvement. The main goal of this work is to assess a color gradient projected to measure the red reflex test in newborns regarding contents and appearance validation, accordance among different observers and nurse’s opinion on the tool applicability after its use. This is a methodological research, quantitative, whose data acquisition happened between May and August 2010 in two methodological steps. Firstly, the proposed instrument was analyzed by three judges. These specialists gave their opinions by means of an evaluation questionnaire in the Likert scale format. The survey covered subjects like goals, structure and presentation, appearance and relevance. In order to quantify their opinions, the answers were restricted to five levels: Absolutely adequate; Adequate with little observations; Partially adequate; Inadequate; It does not apply. In the second step, after collecting the answers and taking into account suggestions from the specialists, we checked the test accordance among different nurses in the color gradient application top the red reflex test. This was made by using a sixty newborns sample. These neonates were in the low risk neonatal sector of a reference public maternity hospital in Fortaleza. Each newborn was examined by two examiners (the researcher and a nurse) simultaneously and independently. The data were treated within PASW 18.0 software. The gradient reliability was calculated by means of the intraclass correlation coefficient. Adjustments were applied to the instrument until its approval. Regarding the contents and appearance evaluation, the judges agreed about the excessive number of gradient colors and they suggested the elimination of several similar patterns. They also recommended to reconsider those patterns with a white center since they could be confused with an altered reflex. Additional suggestions from the specialists pointed to the inclusion of a new color in the instrument as well as a new title to the gradient: color gradient for the little eye test. Most of the answers from the judges were between Absolutely adequate and Adequate with little observations. The specialists considered the developed technology as a complimentary to the practice of the red reflex test, as well as a useful tool for training of professionals to do this test. Good reliability indices were observed (0,928 e 0,894). Such numbers were estimated by the intraclass correlation coefficient. After these considerations, the color gradient was shown to be a valid technology suitable to be considered as a pedagogical tool and as a useful additional instrument on the visual health care. It is expected that the knowledge constructed in this work results in a positive impact on the red reflex test propagation and application.